2013
DOI: 10.14742/ajet.445
|View full text |Cite
|
Sign up to set email alerts
|

Indirect measures of learning transfer between real and virtual environments

Abstract: This paper reports on research undertaken to determine the effectiveness of a 3D simulation environment used to train mining personnel in emergency evacuation procedures, designated the Fires in Underground Mines Evacuation Simulator (FUMES). Owing to the operational constraints of the mining facility, methods for measuring learning transfer were employed which did not require real world performance evaluation. Transfer measures that examined simulator performance relative to real world experience, fidelity as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…[25][26][27][28][29][30] The reviewed literature related to VRS used in overall evacuation training is predominately focused on model crowd response. This research supports the findings of Ribeiro, Almeida, and Rossetti et al 11 and Garrett and MacMahon, 12 who effectively used VRS to train participants in evacuation. This study demonstrates the importance of considering more than one measure of outcome performance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…[25][26][27][28][29][30] The reviewed literature related to VRS used in overall evacuation training is predominately focused on model crowd response. This research supports the findings of Ribeiro, Almeida, and Rossetti et al 11 and Garrett and MacMahon, 12 who effectively used VRS to train participants in evacuation. This study demonstrates the importance of considering more than one measure of outcome performance.…”
Section: Discussionsupporting
confidence: 88%
“…Virtual simulation has been used in evacuation training to model crowd response in multiple studies. [9][10][11][12] In these studies, the effectiveness of the simulation was not tested, but the simulation was used as the environment to measure other variables. In a virtual evacuation environment, Bode, Wagoum, and Coling 9 explored decision-making with 450 participants.…”
Section: Farramentioning
confidence: 99%
See 1 more Smart Citation
“…In short, the study found significantly improved performance for VR participants during a live disaster exercise, 5 which is consistent with other results showing the effectiveness of VR as a training tool. [6][7][8][9][10][11][12] Additionally, the costs of the final live exercise were tracked and quantified along with the costs of the VR training simulations.…”
mentioning
confidence: 99%
“…To provide access to an authentic engineering practice workspace, a VR simulation was used. As discussed above, VR is especially applicable in contexts such as this where access to real engineering work sites may not be feasible or may be hazardous, and VR can effectively emulate the setting through immersive simulations (Freina & Ott, 2015;Garrett & McMahon, 2013;Slater & Sanchez-Vives, 2016).…”
Section: Participants and Settingmentioning
confidence: 99%